Combined optical coherence tomography morphologic and fractional flow reserve hemodynamic assessment of non- culprit lesions to better predict adverse event outcomes in diabetes mellitus patients: COMBINE (OCT–FFR) prospective study. Rationale and design. Issue 1 (December 2016) - Kennedy, Mark; Fabris, Enrico; Ijsselmuiden, Alexander; Nef, Holger; Reith, Sebastian; Escaned, Javier; Alfonso, Fernando; Royen, Niels; Wojakowski, Wojtek; Witkowski, Adam; Indolfi, Ciro; Ottervanger, Jan; et al.
Abstract Background Fractional flow reserve (FFR) is a widely used tool for the identification of ischaemia-generating stenoses and to guide decisions on coronary revascularisation. However, the safety of FFR-based decisions in high-risk subsets, such as patients with Diabetes Mellitus (DM) or vulnerable stenoses presenting thin-cap fibro-atheroma (TCFA), is unknown. This study will examine the impact of optical coherence tomography (OCT) plaque morphological assessment and the identification of TCFA, in combination with FFR to better predict clinical outcomes in DM patients. Methods COMBINE (OCT–FFR) is a prospective, multi-centre study investigating the natural history of DM patients with ≥1 angiographically intermediate target lesion in three subgroups of patients; patients with FFR negative lesions without TCFA (group A) and patients with FFR negative lesions with TCFA (group B) as detected by OCT and to compare these two groups with each other, as well as to a third group with FFR-positive, PCI-treated intermediate lesions (group C). The study hypothesis is that DM patients with TCFA (group B) have a worse outcome than those without TCFA (group A) and also when compared to those patients with lesions FFR ≤0.80 who underwent complete revascularisation. The primary endpoint is the incidence of target lesion major adverse cardiac events (MACE); a composite of cardiac death, myocardial infarction or rehospitalisation for unstable/progressive angina in group Bvs. group A. Conclusion COMBINE (OCT–FFR) is the first prospective study to examine whether the addition of OCT plaque morphological evaluation to FFR haemodynamic assessment of intermediate lesions in DM patients will better predict MACE and possibly lead to new revascularisation strategies. Trial Registration Netherlands Trial Register: NTR5376